Performance Measurement Using the Balanced Scorecard and Business Intelligence in Logistics Companies - Vion Age Tricahyo; Tito Prabowo; Syehka Sofia Arya Larasati; Donatus Ray (STMIK Pringsewu, 2022)
Smart companies should have technological advantages to improve their performance. The research used is a case study of courier and cargo business in collaboration with a rail transportation company. The existing data is processed by applying a Balanced Scorecard and Business Intelligence which aims to support decisions and get great benefits for the company. Data is retrieved for 3 months in the data warehouse. Data operations and processing are carried out to determine which perspectives have a great influence and will help stakeholders in the company get accurate results from patterns. The use of decision tree c 4.5 is used to support the analysis and result in an accuracy of more than 70%. The Kimball Method is used to assist in performance monitoring of data warehouses, customer and financial analysis as well as learning before decision making is made.